2020
DOI: 10.29392/001c.12346
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal oxygen therapy in low- and middle-income countries: a pragmatic review

Abstract: Background We assessed and summarized the peer-reviewed literature on the state of neonatal oxygen therapy in low and lower-middle income countries. Methods A literature search was performed in 3 online databases (Pub Med, EMBASE, CAB Global Health) and amongst USAID’s Service Provision Assessment (SPA) reports for publications pertaining to neonatal oxygen therapy in low and lower-middle income countries over the past 10 years (2007-2017). Results Our search yielded 474 records, of which 26 were relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…While there was a trend toward a greater ratio of male infants being treated in countries with lower income levels, the difference was not statistically significant (eFigure 2 in the Supplement). We hypothesize that high-income countries experiencing a survival of smaller and younger neonates is balanced by low-income countries having less advanced neonatal care and oxygenation protocols …”
Section: Discussionmentioning
confidence: 99%
“…While there was a trend toward a greater ratio of male infants being treated in countries with lower income levels, the difference was not statistically significant (eFigure 2 in the Supplement). We hypothesize that high-income countries experiencing a survival of smaller and younger neonates is balanced by low-income countries having less advanced neonatal care and oxygenation protocols …”
Section: Discussionmentioning
confidence: 99%
“…Although data are scarce, reviews indicate that only a small minority of neonatal units in low-and middleincome countries have access to oxygen blenders. 24,25 In sub-Saharan Africa, for example, a recent study found that only 1% of neonatal units had the capacity to provide blended oxygen to neonates needing oxygen therapy. 26 Moreover, a 2012 survey of neonatologists and pediatricians practicing in metropolitan areas in Africa, Asia, and the Middle East found that although 91% of respondents supported the use of oxygen blending, only one-half reported blending capability, citing financial barriers as a key limiting factor.…”
Section: The Oxygen Blending Gapmentioning
confidence: 99%
“…In India, for example, the incidence of ROP is markedly higher than the incidence reported in high-income countries, and ROP has become the leading cause of avoidable blindness in children. 24,[37][38][39] Moreover, the coronavirus disease 2019 pandemic led to an unprecedented increase in oxygen availability globally. Hundreds of millions of dollars of investments from governments and philanthropic organizations (including the United States Agency for International Development, United Nations Children's Fund, and the World Bank, among others) are being made to rapidly expand oxygen supplies in lowresource settings.…”
Section: The Oxygen Blending Gapmentioning
confidence: 99%
“…In low-resource settings, the presence of respiratory disease does not guarantee receipt of or access to respiratory support [11, 12]. There are no population-based studies that evaluate the distribution of respiratory support between term and preterm infants in low- and middle-income countries (LMICs) [13]. Knowledge of the epidemiology of respiratory support receipt in low-resource settings will help address questions about access and use of respiratory support resources.…”
Section: Introductionmentioning
confidence: 99%